A multicentre integration of a computer‐led follow‐up of prostate cancer is valid and safe. (6th March 2018) - Salem, Hesham A; Caddeo, Giacomo; McFarlane, Jon; Patel, Kunjan; Cochrane, Lynda; Soria, Daniele; Henley, Mike; Lund, Jonathan
Abstract : Objective: To test a computer‐led follow‐up service for prostate cancer in two UK hospitals; the testing aimed to validate the computer expert system in making clinical decisions according to the individual patient's clinical need with a valid model accurately identify patients with disease recurrence or treatment failure based on their blood test and clinical picture. Patients and Methods: A clinical‐decision support system (CDSS) was developed from European (European Association of Urology) and national (National Institute for Health and Care Excellence) guidelines along with knowledge acquired from Urologists. This model was then applied in two UK hospitals to review patients after prostate cancer treatment. These patients' data ( n = 200) were then reviewed by two independent urology consultants (blinded from the CDSS and the other consultant's rating) and the agreement was calculated by kappa statistics for validation. The second endpoint was to verify the system by estimating the system reliability. Results: The two individual urology consultants identified 12% and 15% of the patients to have potential disease progression and recommended their referral to urology care. The kappa coefficient for the agreement between the CDSS and the two consultants was 0.81 ( P < 0.001) and 0.84 ( P < 0.001). The agreement amongst both specialist was also high with k = 0.83 ( P < 0.001). The system reliability was estimated on all cases and this demonstrated 100% repeatability of the decisions. Conclusion: A CDSS follow‐up is a valid model for providing safe follow‐up for prostate cancer.